Wind-down of bank trading books: Operational aspects and hidden costs - Alessandro Santoni; Ghislain Rossignol; Richard Akhouen (European Central Bank (ECB), 2023)
The writing of this article predates by several months the failure of Silicon Valley Bank and the takeover of Credit Suisse which occurred in March 2023. It does not represent the views of the European Central Bank (ECB) and should not be construed as linked to or an advice for the winding down of those banks. This article focuses on some of the operational aspects of winding down a bank's trading book portfolio and discusses the hidden exit costs that can sometimes exist. The article provides a deep dive on valuation principles and exit strategies currently considered by industry practitioners when designing a solvent wind-down plan. It also provides the reader with an overview of key underpinning valuation or pricing concepts, such as 'fair value', 'realisable value' and 'solvent wind-down (SWD) value'. In particular, it argues that the cost to wind down a trading portfolio beyond the usual accounting carrying value might be largely driven by wind-down operating costs (including bank liquidity and funding costs) and two main pricing components, namely the capital valuation adjustment (KVA) and margin valuation adjustment (MVA). We advocate that bank recovery and resolution plans should, in contrast to current practice, properly factor in these additional costs. We also argue that conducting SWD exercises in a pre-crisis period can be very useful in understanding the costs of winding down a trading book. The article follows the ongoing policy discussion on the topic subsequent to the consultative document of the FSB (Financial Stability Board) on the solvent wind-down of derivatives and trading portfolios and the SWD guidance of the SRB (Single Resolution Board).
Keywords: G12; G13; G14; G15; G17; G18; G32; G33; G34; 330; bank's trading book; market risk; solvent wind-down; fair value; realisable value; solvent wind-down value; recovery plan; resolution plan; crisismanagement